HUBUNGAN KONSEP DIRI DENGAN INTERAKSI SOSIAL PESERTA DIDIK KELAS VIII SMP NEGERI 12 PONTIANAK - Tiara Benita; M. Asrori Asrori; Luhur Wicaksono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
Abstract This study aims to obtain a general picture of how the relationship between self-concept and social interaction of students in class VIII State Junior High School 12 Pontianak, how students 'self-concept, how students' social interaction, and whether there is a relationship between self-concept and social interaction of students. The method used in this research is a descriptive method in the form of a survey study that is a procedure with the problem under study by describing or describing to see the relationship between self-concept and social interaction of students in class VIII of SMP Negeri 12 Pontianak, and explained descriptively. Data collection in this study used a questionnaire. Based on the results and questionnaire data processing, that overall students' self-concept reached an actual score of 6786 from an ideal score of 8910, meaning that 76% was in the "Good" category, and overall social interaction of students reached an actual score of 7074 from a score of 8910, meaning that it reached 79 % is in the "Good" category. So in general the results of this study indicate that there is a significant positive relationship between self-concept and students' social interactions.Keywords: Self Concept, Social Interaction